A Klinefelter boy with congenital adrenal hyperplasia: too much or too little androgens? - Zanella, Giada; Tornese, Gianluca; Mascheroni, Elisabetta; Faleschini, Elena; Ventura, Alessandro; Barbi, Egidio (Ital J Pediatr, 2018)
BACKGROUND: The simultaneous occurrence of Klinefelter Syndrome (KS) and Congenital Adrenal Hyperplasia (CAH) is an exceptional event: there are just three case reports (two children and a 51 years old man) describing males affected by both KS and 21OHD (21-hydroxylase deficiency) CAH, the first causing androgen deficiency, the latter leading to androgen excess. CASE REPORT: We report the 4th case of association of KS and CAH in a young man with CAH with good androgen control and with normal secondary sex characteristics, whose Klinefelter syndrome was diagnosed because of reduced testicular volume. He was the first reported case of association of KS and CAH who started androgen replacement therapy in the pubertal age and whose pubertal development was described and followed up step by step. CONCLUSION: In a boy with CAH and small testicular volume, it's important to consider that hypogonadism may be masked by the adrenal androgens excess and a karyotype should be performed once testicular adrenal rests have been ruled out.
Keywords: Adolescent; Adrenal Hyperplasia, Congenital; Androgens; Follow-Up Studies; Hormone Replacement Therapy; Humans; Klinefelter Syndrome; Male; Rare Diseases; Risk Assessment; Testis

The Klinefelter syndrome is associated with high recurrence of copy number variations on the X chromosome with a potential role in the clinical phenotype. - Rocca, M S; Pecile, V; Cleva, L; Speltra, E; Selice, R; Di Mambro, A; Foresta, C; Ferlin, A (Andrology, 2016)
The Klinefelter syndrome (KS) is the most frequent sex chromosomal disorder in males, characterized by at least one supernumerary X chromosome (most frequent karyotype 47,XXY). This syndrome presents with a broad range of phenotypes. The common characteristics include small testes and infertility, but KS subjects are at increased risk of hypogonadism, cognitive dysfunction, obesity, diabetes, metabolic syndrome, osteoporosis, and autoimmune disorders, which are present in variable proportion. Although part of the clinical variability might be linked to a different degree of testicular function observed in KS patients, genetic mechanisms of the supernumerary X chromosome might contribute. Gene-dosage effects and parental origin of the supernumerary X chromosome have been suggested to this regard. No study has been performed analyzing the genetic constitution of the X chromosome in terms of copy number variations (CNVs) and their possible involvement in phenotype of KS. To this aim, we performed a SNP arrays analysis on 94 KS and 85 controls. We found that KS subjects have more frequently than controls X-linked CNVs (39/94, [41.5%] with respect to 12/42, [28.6%] of females, and 8/43, [18.6%] of males, p < 0.01). The number of X-linked CNVs in KS patients was 4.58 ± 1.92 CNVs/subject, significantly higher with respect to that found in control females (1.50 ± 1.29 CNVs/subject) and males (1.14 ± 0.37 CNVs/subject). Importantly, 94.4% X-linked CNVs in KS subjects were duplications, higher with respect to control males (50.0%, p < 0.001) and females (83.3%, p = 0.1). Half of the X-linked CNVs fell within regions encompassing genes and most of them (90%) included genes escaping X-inactivation in the regions of X-Y homology, particularly in the pseudoautosomal region 1 (PAR1) and Xq21.31. This study described for the first time the genetic properties of the X chromosome in KS and suggests that X-linked CNVs (especially duplications) might contribute to the clinical phenotype.

The Kalash genetic isolate: ancient divergence, drift, and selection. - Ayub, Qasim; Mezzavilla, Massimo; Pagani, Luca; Haber, Marc; Mohyuddin, Aisha; Khaliq, Shagufta; Mehdi, Syed Qasim; Tyler-Smith, Chris (Am J Hum Genet, 2015)
The Kalash represent an enigmatic isolated population of Indo-European speakers who have been living for centuries in the Hindu Kush mountain ranges of present-day Pakistan. Previous Y chromosome and mitochondrial DNA markers provided no support for their claimed Greek descent following Alexander III of Macedon's invasion of this region, and analysis of autosomal loci provided evidence of a strong genetic bottleneck. To understand their origins and demography further, we genotyped 23 unrelated Kalash samples on the Illumina HumanOmni2.5M-8 BeadChip and sequenced one male individual at high coverage on an Illumina HiSeq 2000. Comparison with published data from ancient hunter-gatherers and European farmers showed that the Kalash share genetic drift with the Paleolithic Siberian hunter-gatherers and might represent an extremely drifted ancient northern Eurasian population that also contributed to European and Near Eastern ancestry. Since the split from other South Asian populations, the Kalash have maintained a low long-term effective population size (2,319-2,603) and experienced no detectable gene flow from their geographic neighbors in Pakistan or from other extant Eurasian populations. The mean time of divergence between the Kalash and other populations currently residing in this region was estimated to be 11,800 (95% confidence interval = 10,600-12,600) years ago, and thus they represent present-day descendants of some of the earliest migrants into the Indian sub-continent from West Asia.
Keywords: Asia; Asian Continental Ancestry Group; Chromosomes, Human, Y; Demography; DNA, Mitochondrial; European Continental Ancestry Group; Genetic Drift; Genetics, Population; Haplotypes; History, Ancient; Humans; Male; Pakistan; Phylogeny

Kinetic Profiles of Inflammatory Mediators in the Conjunctival Sac Fluid of Patients upon Photorefractive Keratectomy. - Tisato, Veronica; Perri, Paolo; Rimondi, Erika; Melloni, Elisabetta; Lamberti, Giuseppe; Milani, Daniela; Secchiero, Paola; Zauli, Giorgio (Mediators Inflamm, 2015)
Photorefractive keratectomy (PRK) represents a therapeutic option to remodel corneal stroma and to compensate refractive errors, which involves inflammatory and/or regenerative processes. In this context, the modulation of cytokines/chemokines in the conjunctival sac fluid and their role in the maintenance of the corneal microenvironment during the healing process upon refractive procedures has not been deeply investigated. In this study, serial samples of conjunctival sac fluid of patients (n = 25) undergoing PRK were harvested before and at different time points after surgery. The levels of 29 cytokines/chemokines/growth factors involved in inflammatory/immune processes were measured with a multiplex array system. The results have firstly highlighted the different pattern of cytokine expression between the microenvironment at the anterior surface of the eye and the systemic circulation. More importantly, the kinetic of modulation of cytokines/chemokines at the conjunctival level following PRK revealed that while the majority of cytokines/chemokines showed a significant decrease, MCP-1 emerged in light of its pronounced and significant increase soon after PRK and during the follow-up. This methodological approach has highlighted the role of MCP-1 in the healing process following PRK and has shown a potential for the identification of expression/modulation of soluble factors for biomarker profiling in ocular surface diseases.

Knockdown of MVK does not lead to changes in NALP3 expression or activation. - Celsi, Fulvio; Piscianz, Elisa; Romano, Maurizio; Crovella, Sergio (J Inflamm (Lond), 2015)
BACKGROUND: Mutations in the Mevalonate Kinase gene (MVK) are causes of a rare autoinflammatory disease: Mevalonate Kinase Deficiency and its more acute manifestation, Mevalonic Aciduria. The latter is characterized, among other features, by neuroinflammation, developmental delay and ataxia, due to failed cerebellar development or neuronal death through chronic inflammation. Pathogenesis of neuroinflammation in Mevalonate Kinase Deficiency and Mevalonic Aciduria has not yet been completely clarified, however different research groups have been suggesting the inflammasome complex as the key factor in the disease development. A strategy to mimic this disease is blocking the mevalonate pathway, using HMG-CoA reductase inhibitors (Statins), while knock-out mice for Mevalonate Kinase are non-vital and their hemyzygous (i.e only one copy of gene preserved) littermate display almost no pathological features. FINDINGS: We sought to generate a murine cellular model closely resembling the pathogenic conditions found in vivo, by direct silencing of Mevalonate Kinase gene. Knockdown of Mevalonate Kinase in a murine microglial cellular model (BV-2 cells) results in neither augmented NALP3 expression nor increase of apoptosis. On the contrary, statin treatment of BV-2 cells produces an increase both in Mevalonate Kinase and NALP3 expression. CONCLUSIONS: MKD deficiency could be due or affected by protein accumulation leading to NALP3 activation, opening novel questions about strategies to tackle this disease.